Pulsed laser-arc welding of carbon steel - Жерносеков, Анатолий Максимович; Хаскин, Владислав Юрьевич; Набок, Тарас Николаевич (Eastern-European Journal of Enterprise Technologies, 2014)
The urgency of this work is associated with lowering of thermal impact on base metal during welding that promotes minimizing residual thermal deformations of items being welded, for instance, railway car or ship hull. This, in its turn, simplifies or completely eliminates the complex operation of finish straightening. However, one of the welding technologies reducing the magnitude of deformations, compared to currently applied arc welding, is laser welding. Its application, however, is limited by high requirements to edge preparation. In order to lower these requirements, it is rational to use hybrid laser-arc welding with application of consumable-electrode arc. Here, lowering of arc pressure on the weld pool and heat input into the metal being welded can be achieved due to pulse modulation of arc and laser components of the hybrid process. The work shows that it is rational to apply simultaneous pulse modulation of the welding arc and laser radiation with the frequency close to that of natural vibrations of the weld pool in laser welding, in order to improve formation of weld upper bead and increase the penetration depth. Modulation frequencies can be equal to or multiple of each other, exceeding the values of arc pulse feed frequencies.